Dampak VAR Terhadap Keputusan Wasit dan Kualitas Pertandingan Sepak Bola - Muhamad Davin Akbar Firdaus; Cahaya Tresna Afra Syaefu; Chandra Supriatna; Falih Athofa Ramzar; Luqman Muhammad Fadhlul Nul Hakim; Agus Mulyana (Pusat Riset dan Inovasi Nasional, 2024)
Football, as the world's most popular sport, has undergone significant changes with the introduction of Video Assistant Referee (VAR) technology. Designed to enhance referee decision accuracy through video replays, VAR has been widely adopted in major competitions despite initial controversy. Studies have shown its effectiveness in reducing referee errors in crucial incidents such as goals, penalties, and red cards. In Indonesia, VAR usage could enhance fairness and reduce match controversies, although domestic leagues currently rely on referees without technological assistance. While VAR offers numerous benefits, including improved referee standards and viewer experience, criticism regarding game flow disruption and inconsistent application persists. Moving forward, it is crucial to balance accuracy and fairness with the excitement of the game and ensure good collaboration among all football stakeholders.